2010
DOI: 10.1186/1471-2393-10-11
|View full text |Cite
|
Sign up to set email alerts
|

APCR, factor V gene known and novel SNPs and adverse pregnancy outcomes in an Irish cohort of pregnant women

Abstract: BackgroundActivated Protein C Resistance (APCR), a poor anticoagulant response of APC in haemostasis, is the commonest heritable thrombophilia. Adverse outcomes during pregnancy have been linked to APCR. This study determined the frequency of APCR, factor V gene known and novel SNPs and adverse outcomes in a group of pregnant women.MethodsBlood samples collected from 907 pregnant women were tested using the Coatest® Classic and Modified functional haematological tests to establish the frequency of APCR. PCR-Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
6
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 68 publications
1
6
0
Order By: Relevance
“…In this study, we identified thrombophilic mutations in 66% of our positive APCR (acquired plus inherited) group ( n = 140). One of those subjects had 2 mutations in the FV gene, FVL and FV Cambridge-G1091C, at two cleavages sites of FV for APC [21]. This subject was also found in this study to be a carrier of MTHFR-C677T mutation.…”
Section: Discussionsupporting
confidence: 61%
See 2 more Smart Citations
“…In this study, we identified thrombophilic mutations in 66% of our positive APCR (acquired plus inherited) group ( n = 140). One of those subjects had 2 mutations in the FV gene, FVL and FV Cambridge-G1091C, at two cleavages sites of FV for APC [21]. This subject was also found in this study to be a carrier of MTHFR-C677T mutation.…”
Section: Discussionsupporting
confidence: 61%
“…DNA probe hybridisation analysis and/or DNA sequencing was applied for Arg 679 detection as described [21]. One hundred and forty APCR-positive subjects and 31 APCR-negative subjects were tested for all mutations.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Space limitations prevented us from more detailed reporting of the methods and results of our systematic review. We are familiar with the study by Kjellberg et al ., as it was one of the seven full‐text articles that were retrieved in the systematic review process. Their report was independently assessed by two reviewers (M.R.…”
mentioning
confidence: 99%
“…This would have given an opportunity to draw stronger final conclusions. The authors have chosen to add only the results from their new study and the results from one other study with 29 FVL carriers [4]. Addendum U Kjellberg and M Hellgren wrote the letter and approved its submission.…”
mentioning
confidence: 99%